SPK PENENTUAN DEBITUR YANG MEMILIKI TUNGGAKAN KREDIT MENGGUNAKAN METODE AHP-TOPSIS (STUDI KASUS: BPR IRIAN SENTOSA CABANG TIMIKA) - , IMELDA O. PAKASI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was made based on the needs of the credit section head in determining priorities billing credit arrears on BPR Irian Sentosa Timika branch. Appropriate decisions related to it, is one of the determining factors in maintaining the health of banks. Prioritization of collecting credit arrears, based on eight criteria variable, and this research indicate that the priority of collection credit arrears can be determined through Analitycal Hierarchy Process (AHP) method and Technique for Order Preference by Similirarity to Ideal Solution (TOPSIS) method. AHP method is used to find the weight of criteria variables, scoring collectability, the type of arrears, and the type of credit, while TOPSIS is used to find the final score and the rank of each alternatives. Priority of collecting credit arrears based on credit arrears that highly affect the percentage value of NPL (Non Performing Loan), and from the final score, status of each debitor are known. Whether the status is highest risk, very risk, risk or less risk. Higher the score, higher the preference of the alternative. Result of this research indicate that the utility of AHP and TOPSIS method as a decision support system model that can help credit section head of BPR Irian Sentosa Timika branch, and based on arrears data at January 2014, indicate that those method are considered appropriate in giving priority collecting credit arrears.